A Diagnostic Significance of MIG (Monokine Induced by Gamma Interferon) and IP-10 (Interferon gamma-induced protein 10) Chemokines in Alopecia Areata - Ali, Zinah Abbass; Shemran, Khawla A.; Behayaa, Hiba Resheed (Medical Science Journal for Advance Research, 2025)
Background: The condition of Alopecia Areata (AA) is a type of autoimmune disease that results in the loss of hair in patches. Some immunologically active chemokines, such as MIG (CXCL9) and IP-10 (CXCL10), which are stimulated by interferon-gamma, are believed to be involved in the inflammatory processes of AA, and may contribute to its development. Objectives: To measure the serum levels of MIG and IP-10 in patients with Alopecia Areata and evaluate those levels for possible differential diagnostic significance. Methods: The study consisted of 60 patients with AA, alongside 60 age-matched healthy controls. The participants were sourced from dermatology clinics where they were evaluated clinically. Patients with complex systemic autoimmune diseases, active infections, or those who had recently undergone immunosuppressive treatments were not eligible for the study. Serum levels of MIG and IP-10 were quantified using the ELISA technique. Correlation studies as well as ROC curve analysis were performed for the statistical evaluation. Results: In comparison to controls, AA patients had a mean serum MIG level that was significantly higher at (864.13 ± 201.08 pg/ml) while controls had 299.04 ± 130.4 pg/ml (p<0.01). Moreover, AA patients also had elevated IP-10 levels 504.61 ± 122.2 pg/ml compared to controls 297.9 ± 77.3 pg/ml (p<0.01). Within patients, Pearson correlation showed moderate-to-strong correlation of MIG with IP-10, BMI, and age. In ROC curve analysis, MIG had an AUC of 0.972 (sensitivity 80%, specificity 87%) whereas IP-10 had an AUC of 0.89 (sensitivity 62%, specificity 76%). Conclusion: AA patients showed significantly elevated levels of MIG and IP-10 indicating possible involvement in pathogenesis. Particularly, MIG showed strong diagnostic capability. These findings suggest that these chemokines may be potential biomarkers for the early diagnosis and follow-up of AA.